Regulation of Ribosomal S6 Protein Kinase-p90(rsk), Glycogen Synthase Kinase 3, and β-Catenin in Early Xenopus Development - Torres, Monica A. (American Society for Microbiology, 1999)
β-Catenin is a multifunctional protein that binds cadherins at the plasma membrane, HMG box transcription factors in the nucleus, and several cytoplasmic proteins that are involved in regulating its stability. In developing embryos and in some human cancers, the accumulation of β-catenin in the cytoplasm and subsequently the nuclei of cells may be regulated by the Wnt-1 signaling cascade and by glycogen synthase kinase 3 (GSK-3). This has increased interest in regulators of both GSK-3 and β-catenin. Searching for kinase activities able to phosphorylate the conserved, inhibitory-regulatory GSK-3 residue serine 9, we found p90(rsk) to be a potential upstream regulator of GSK-3. Overexpression of p90(rsk) in Xenopus embryos leads to increased steady-state levels of total β-catenin but not of the free soluble protein. Instead, p90(rsk) overexpression increases the levels of β-catenin in a cell fraction containing membrane-associated cadherins. Consistent with the lack of elevation of free β-catenin levels, ectopic p90(rsk) was unable to rescue dorsal cell fate in embryos ventralized by UV irradiation. We show that p90(rsk) is a downstream target of fibroblast growth factor (FGF) signaling during early Xenopus development, since ectopic FGF signaling activates both endogenous and overexpressed p90(rsk). Moreover, overexpression of a dominant negative FGF receptor, which blocks endogenous FGF signaling, leads to decreased p90(rsk) kinase activity. Finally, we report that FGF inhibits endogenous GSK-3 activity in Xenopus embryos. We hypothesize that FGF and p90(rsk) play heretofore unsuspected roles in modulating GSK-3 and β-catenin.